Antecedents of employees' e-training participation in a Malaysian private company - Tan, Yen Ying; Mohd Rasdi, Roziah (Universiti Putra Malaysia Press, 2017)
Previous literature indicated that people tend to have lower motivation and level of participation in e-training. This case study aims to shed light on the factors that contribute to employees' e-training participation. It examines the influence of personality traits i.e. computer self-efficacy and self-esteem and attitudinal disposition i.e. technology acceptance, job satisfaction and organisational commitment on employees' e-training participation. Results of the study indicate that all of the selected predictors were correlated positively with employees' participation in e-training. The three most dominant factors that influenced employees' participation in e-training were computer self-efficacy, technology acceptance and organisational commitment. The implications and conclusions of the study are clarified.